Identification of bacteria utilizing biphenyl, benzoate, and naphthalene in long-term contaminated soil - Uhlik, Ondrej; Wald, Jiri; Strejcek, Michal; Musilova, Lucie; Ridl, Jakub; Hroudova, Miluse; Vlcek, Cestmir; Cardenas, Erick; Mackova, Martina; Macek, Tomas (PLoS One, 2012)
Bacteria were identified associated with biodegradation of aromatic pollutants biphenyl, benzoate, and naphthalene in a long-term polychlorinated biphenyl- and polyaromatic hydrocarbon-contaminated soil. In order to avoid biases of culture-based approaches, stable isotope probing was applied in combination with sequence analysis of 16 S rRNA gene pyrotags amplified from (13)C-enriched DNA fractions. Special attention was paid to pyrosequencing data analysis in order to eliminate the errors caused by either generation of amplicons (random errors caused by DNA polymerase, formation of chimeric sequences) or sequencing itself. Therefore, sample DNA was amplified, sequenced, and analyzed along with the DNA of a mock community constructed out of 8 bacterial strains. This warranted that appropriate tools and parameters were chosen for sequence data processing. (13)C-labeled metagenomes isolated after the incubation of soil samples with all three studied aromatics were largely dominated by Proteobacteria, namely sequences clustering with the genera Rhodanobacter Burkholderia, Pandoraea, Dyella as well as some Rudaea- and Skermanella-related ones. Pseudomonads were mostly labeled by (13)C from naphthalene and benzoate. The results of this study show that many biphenyl/benzoate-assimilating bacteria derive carbon also from naphthalene, pointing out broader biodegradation abilities of some soil microbiota. The results also demonstrate that, in addition to traditionally isolated genera of degradative bacteria, yet-to-be cultured bacteria are important players in bioremediation. Overall, the study contributes to our understanding of biodegradation processes in contaminated soil. At the same time our results show the importance of sequencing and analyzing a mock community in order to more correctly process and analyze sequence data.
Keywords: Naphthalenes; biodegradace; Biphenyl Compounds; sekvenční analýza DNA; bifenylové sloučeniny; naftaleny; Soil Microbiology; Sequence Analysis, DNA; Soil Pollutants; DNA bakterií; Isotope Labeling; Benzoates; Base Sequence; izotopy uhlíku; Carbon Isotopes; látky znečišťující půdu; půdní mikrobiologie; Biodegradation, Environmental; Phylogeny; sekvence nukleotidů; izotopové značení; fylogeneze; benzoáty; Bacteria; DNA, Bacterial